KONSEP DASAR DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM DUNIA PENDIDIKAN - Hana Tadzkiya; Munjin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of information technology has driven transformation in educational management, including the implementation of Management Information Systems (MIS). This study aims to examine the basic concepts and implementation of MIS in the field of education, using a descriptive qualitative approach through literature review. MIS in educational settings covers various aspects, such as student data management, learning outcome reporting, teacher performance monitoring, and financial management. The integrated implementation of MIS enables increased efficiency, effectiveness, and transparency in the delivery of educational services. In addition, the use of information technology tools such as E- Report Cards and Financial MIS can accelerate administrative processes and support strategic decision-making in Islamic educational institutions. This study emphasizes the importance of a comprehensive understanding of MIS concepts and practices to enhance the quality of education in the digital era.